Environmental Influences on the Growing Season Duration and Ripening of Diverse Miscanthus Germplasm Grown in Six Countries - Nunn, Christopher; Hastings, Astley Francis St. John; Kalinina, Olena; Özgüven, Mensure; Schüle, Heinrich; Tarakanov, Ivan G.; Van Der Weijde, Tim; Anisimov, Aleksander A.; Iqbal, Yasir; Kiesel, Andreas; Khokhlov, Nikolay F.; McCalmont, Jon P.; et al. (Frontiers in Plant Science, 2017)
The development of models to predict yield potential and quality of a Miscanthus crop must consider climatic limitations and the duration of growing season. As a biomass crop, yield and quality are impacted by the timing of plant developmental transitions such as flowering and senescence. Growth models are available for the commercially grown clone Miscanthus x giganteus (Mxg), but breeding programs have been working to expand the germplasm available, including development of interspecies hybrids. The aim of this study was to assess the performance of diverse germplasm beyond the range of environments considered suitable for a Miscanthus crop to be grown. To achieve this, six field sites were planted as part of the EU OPTIMISC project in 2012 in a longitudinal gradient from West to East: Wales - Aberystwyth, Netherlands - Wageningen, Stuttgart – Germany, Ukraine - Potash, Turkey - Adana and Russia - Moscow. Each field trial contained three replicated plots of the same 15 Miscanthus germplasm types. Through the 2014 growing season, phenotypic traits were measured to determine the timing of developmental stages key to ripening; the tradeoff between growth (yield) and quality (biomass ash and moisture content). The hottest site (Adana) showed an accelerated growing season, with emergence, flowering and senescence occurring before the other sites. However, the highest yields were produced at Potash, where emergence was delayed by frost and the growing season was shortest. Flowering triggers varied with species and only in Mxg was strongly linked to accumulated thermal time. Our results show that a prolonged growing season is not essential to achieve high yields if climatic conditions are favourable and in regions where the growing season is bordered by frost, delaying harvest can improve quality of the harvested biomass.